Performance Analysis Of Multilevel Heliostat Field Layout - Aldulaimi, Ra'ad K Mohammed; Söylemez, Mehmet Sait (Fırat University, 2016)
A novel heliostat field layout is suggested by dividing specified heliostats located farthest from the tower and exhibiting low optical efficiency into strips and increasing the height for these strips with varying heights, based on the consideration of no blocking. A novel geometrical equation is presented for this purpose, and the results indicate an increase in the total annual efficiency of the field. The proposed layout is implemented on an optimized heliostat field consisting of 2650 SENER heliostats, based on the data obtained using Gemasolar in Seville, Spain, which is used as a reference in this work. Each heliostat position is specified using an optimization algorithm that refines previously proposed models, and two parameters are added to this model to further optimize the heliostat layout.

Güneş tarlalarında optik verimliliği temelde helyostatlardaki gölgelemeleri engelleyerek arttırmak amacıyla, kademeli değişken yükseklik uygulamasının etkisi araştırılmış ve düşük optik verimlilik değerlerinin düzeldiği görülmüştür. Bu amaçla, geliştirilen bir geometrik denklem sunulmuş ve sonuçlarda güneş tarlasında yıllık verimin arttığı hesaplanmıştır. Önceden optimize edilmiş 2650 helyostatlı SENER güneş tarlası için önerilen yöntem kullanılarak, İspanyanın Sevilla şehrinde bulunan Gemasolar helyostat sistemi için alınan sonuçlar önceki değerlerle karşılaştırılmak suretiyle mukayeseli olarak kontrol edilerek doğrulanmıştır. Her bir helyostat pozisyonu için optimizasyon algoritması tanımlanarak önceki modellemelerin önüne geçen ve iki yeni parametreyi de ekleyerek helyostat yerleştirilmesini optimize eden bir yeni model önerilmiştir.
Değişken Seviyeli Heliostat Uygulamalı Güneş Tarlalarının Performans Değerlendirmesi